A Multi-Custodians Distributed Storage Mechanism for DTN Storage-based Congestion Problem - Lai, Ching-Neng (Malaysian Journal of Computer Science, 2016)
Nowadays, distributed storage is adopted to alleviate Delay-tolerant networking (DTN) congestion, but reliability transmission during the congestion period remains an issue. In this paper, we propose a multi-custodians distributed storage (MCDS) framework that includes a set of algorithms to determine when should appropriate bundles be migrated (or retrieved) to (or from) the suitable custodians, so that we can solve DTN congestion and improve reliability transmission simultaneously. MCDS adopts multiple custodians to temporarily store the duplications of migrated bundle for releasing DTN congestion. Thus, MCDS has more opportunities to retrieve the migrated bundles when network congestion is mitigated. Two performance metrics are used to evaluate the simulation results: the goodput ratio (GR) that represents QoS of data transmission, and the retrieved loss ratio (RLR) that reflects the performance of reliability transmission. We also use another distributed storage mechanism based on single-custodian distributed storage (SCDS) to evaluate MCDS. Simulation results show that MCDS has better GR and RLR in almost all simulation cases. For various scenarios, the GR and RLR of MCDS are in the range of 10.6%-18.4% and 23.2%-36.8%, respectively, which are higher than those of SCDS.